Legal regime ground water in Peru - Cairampoma Arroyo, Alberto (2016)
This article studies the legal regime of groundwater by analyzing the context of integrated water resources management and recognizing its definition and characteristics.Furthermore, it analyses the ownership of ground water, the planning regime applicable, the exploration and exploitation activities, their authorization certificates, the activity of supervision over them, and finally the article describes the special schemes for management and limitation recognized in Peruvian law.